2017
DOI: 10.3390/molecules22071175
|View full text |Cite
|
Sign up to set email alerts
|

Evodiamine Exerts an Anti-Hepatocellular Carcinoma Activity through a WWOX-Dependent Pathway

Abstract: Evodiamine is one of the main components isolated from Evodia rutaecarpa, and it has been reported to exert inhibitory effects on cancers by anti-proliferative and apoptosis-inducing activities. Although the anti-cancer activity of evodiamine has been identified, the precise mechanisms of this action remain obscure. While previous studies indicated that evodiamine exerts anti-tumor effects through inhibiting β-catenin activity, and WW domain-containing oxidoreductase (WWOX) regulates β-catenin accumulation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…And the inhibition of WWOX reversed the cytotoxic effect of evodiamine. As such, the anti-hepatocellular carcinoma activity of evodiamine was linked with the activation of WWOX [ 46 ]. Activator protein 1 (AP-1) is required for tumor promotion [ 47 ].…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…And the inhibition of WWOX reversed the cytotoxic effect of evodiamine. As such, the anti-hepatocellular carcinoma activity of evodiamine was linked with the activation of WWOX [ 46 ]. Activator protein 1 (AP-1) is required for tumor promotion [ 47 ].…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…Evodiamine (EV) is a natural alkaloid and a primary biologically active ingredient of Evodia rutaecarpa, a medicinal plant used in traditional Chinese medicine (Hu et al 2017). Pharmacological studies have shown that EV binds to a variety of proteins, and so it can be used as a multitarget compound for tumors, obesity, pain, inflammation, cardiovascular disease, and Alzheimer's disease (Cai et al 2014;Wang et al 2013;Wu et al 2013;Yu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A number of drugs isolated from nature have shown potential against different cancers including prostate [20][21][22][23][24][25][26][27][28][29][30][31][32]. Evodiamine (EVO) is an indoloquinazoline alkaloid reported to have various pharmacological effects including anti-proliferation [33][34][35], and anti-tumor properties [36,37], and can cause both cell cycle arrest [38,39] and apoptosis [40,41] in vitro and in vivo. According to previous studies, EVO can effectively block PI3K/protein kinase B (Akt), MAPK, and nuclear factor kappa B (NF-κB) signaling pathways and enhance apoptosis [33,[42][43][44].…”
Section: Introductionmentioning
confidence: 99%